Exploring the role of community empowerment in urban poverty eradication in Kuala Lumpur, Malaysia - Dass, Mahaganapathy; Kunasekaran, Puvaneswaran; Kaur, Charanjit; Gill, Sarjit S. (Multidisciplinary Digital Publishing Institute, 2022)
The main purpose of this study was to holistically understand the role of empowerment in urban poverty eradication of the Indian community in the urban areas of the Klang Valley, Malaysia. The poverty eradication effectiveness was tested by analysing community empowerment domains and MyKasih programme run by a non-governmental organisation. There are numerous studies conducted to understand the issues of poverty in Malaysia. However, few studies have so far focused on the minority community in Malaysia. Moreover, there is no recent study to test the effectiveness of any governmental or NGO’s poverty eradication efforts on this minority community. This study utilised a qualitative approach and an in-depth interview was used to gather the data. The respondents were single mothers living in a poverty-stricken area in the capital city of Malaysia.